Successful Stent Implantation and Lower MACE Rates with OAS - Rizzo, Toni (MD Conference Express, 2014)
Calcified coronary lesions are difficult to treat for several reasons. Researchers of the Evaluate the Safety and Efficacy of OAS in Treating Severely Calcified Coronary Lesions trial [ORBIT II; NCT01092416] examined the safety and efficacy of the coronary Orbital Atherectomy System (OAS) to prepare de novo, severely calcified coronary lesions for enabling stent placement.